<span>
ft =</span><span>yd * 3.0000 is the operation you would use</span>
F(-4)=G(-4) because when the two lines cross over the f line is at the -4 and same with G
Answer: x= -1
y= -2
Step-by-step explanation:
-4x+3y= -2
y=x-1
-------------------
-4x+3(x-1)= -2
-4x+3x-3= -2
-x=1
x= -1
y=-1-1
y=-2
2² - y - 5 = 0
Evaluate the power.
4 - y - 5 = 0
Calculate the sum or difference.
-1 - y = 0
Move constant to the right side and change its sign.
-y = 1
Change the signs on both sides of the equation.
y = -1